Structure and individual anatomical variability of the biventral lobule of the human cerebellum. - Maryenko, N. I.; Stepanenko, O. Yu. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Morphological changes of the cerebellar lobules are found in many congenital and acquired diseases of the cerebellum, but the information on the normal structure of the cerebellar lobules do not take into account the peculiarities of individual anatomical variability, sex and age characteristics. Objective - to investigate features of individual variability and variant anatomy of the lobule VIII of the human cerebellar hemispheres. Methods. The study was conducted on 100 cerebellums of people of both sexes, who died of causes unrelated to brain pathology (20–95 years old). Features of the shape, branching of white matter of lobule VIII, number, shape and location of folia of gray matter on parasagittal sections of the cerebellar vermis were investigated. Results. Complex branched white matter is the basis of the VIII lobule of human cerebellar hemispheres. Lobule is divided into two parts: lobule VIIIA (rostral part) and VIIIB (caudal part). The main branch of the white matter is dichotomously divided into different number of secondary branches. We described 3 variants of branching of white matter of lobule VIII. First variant of lobule consists of main trunk of white matter, which is divided into two secondary branches. The white matter is Y-shaped. Second variant of lobule includes two branches of white matter which are connected only in the basal part. The white matter is V-shaped. Third variant of lobule includes two branches of white matter which are not connected. The most common variant forms of the rostral part lobule VIII is the 3rd variant, and the caudal part – 1st variant. Conclusion. Described variants of the shape of the cerebellar lobule VIII can be used as criteria standards of modern diagnostic imaging techniques for the diagnosis of various diseases of the CNS.